2004
DOI: 10.1016/s0304-8853(03)00498-0
|View full text |Cite
|
Sign up to set email alerts
|

On the competition between ferromagnetic and antiferromagnetic states in Sr2MnMoO6

Abstract: It is argued that the magnetic behavior of Sr 2 MnMoO 6 is determined by the existence of two total energy minima corresponding to the metallic ferromagnetic and insulating antiferromagnetic states, which may be nearly degenerate depending on the magnitude of the breathing distortion.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…As can be seen from figure 5, density of states of spin up channel crosses the Fermi level while there is an energy gap of 0.65 eV at the spin down channel which is close to what has been reported (E gap = 0.67 eV) for Sr 2 MnCrO 6 [23]. Therefore, the double perovskite SMVO has a HM nature similar to some other reported double perovskite compounds [18][19][20][21][22][23][24][25].…”
Section: Magnetic and Electronic Propertiessupporting
confidence: 85%
See 1 more Smart Citation
“…As can be seen from figure 5, density of states of spin up channel crosses the Fermi level while there is an energy gap of 0.65 eV at the spin down channel which is close to what has been reported (E gap = 0.67 eV) for Sr 2 MnCrO 6 [23]. Therefore, the double perovskite SMVO has a HM nature similar to some other reported double perovskite compounds [18][19][20][21][22][23][24][25].…”
Section: Magnetic and Electronic Propertiessupporting
confidence: 85%
“…The Sr-based double perovskites have generated a lot of interest with the discovery of the room-temperature colossal magnetoresistance (CMR) in Sr 2 FeMoO 6 [20]. The quest to find HM material candidates in Sr 2 BB′O 6 compounds concentrated on the study of structural, electronic and magnetic properties [21,22]. For instance, Liu et al investigated the electronic and magnetic properties of Sr 2 BB′O 6 in which B and B′ are 3d transition metals based on density functional theory (DFT) calculations with both GGA and GGA + U approaches.…”
Section: Introductionmentioning
confidence: 99%
“…Ordered double perovskites, A 2 BB′O 6 , are a good baseline structure for determining suitable HM material candidates, because there are a variety of combinations for substituting the A-site or B-site elements. In previous research, HM compounds were found, such as Sr 2 FeWO 6 [6], Sr 2 FeReO6 [15,16], Sr 2 MnMoO6 [16], Sr 2 CuOsO 6 [17], Sr 2 VOsO 6 [18], Sr 2 NiRuO 6 [19], Sr 2 FeTiO 6 [20], Sr 2 CrMoO 6 [12,21], Sr 2 CoMoO 6 [12], Sr 2 CrReO 6 [11,15] and Sr 2 CrWO 6 [14,22] for the same ion Sr on the A-site with different combinations of B-site elements. Sr 2 MnMoO 6 [8] and Ba 2 MnMoO 6 [23] represent A-site substitution with fixed B-site elements.…”
Section: Introductionmentioning
confidence: 94%
“…The close relation between conduction electrons and magnetic electrons makes an exchange interaction between ions of the same element; this explains the link between the electronic and magnetic properties in double perovskite by scanning the range of different materials with several behaviours from a metallic ferromagnetic or ferrimagnetic to antiferromagnetic or paramagnetic one [11]. There are many studies of half-metallic ferromagnetic compounds due to their potential technological application such as Sr 2 CrWO 6 [12], Sr 2 FeReO 6 [13,14], Pb 2 FeMoO 6 [15], Sr 2 FeWO 6 [16], Sr 2 CoMoO 6 [17], Sr 2 CrMoO 6 [18], Sr 2 FeTiO 6 [19] and recently Sr 2 GdReO 6 [20]. Pb 2 FeTaO 6 is among these DP's which has received a lot of interest from the authors Brixel et al [21,22], they have experimentally worked on the growth of single crystal of this material for studding both of electrical and optical measurements.…”
Section: Introductionmentioning
confidence: 99%